Plasma CCL3 predicts adverse heart failure outcomes in patients with arrhythmogenic cardiomyopathy - Hao Cui; Songren Shu; Ningning Zhang; Mangyuan Wang; Tianshuo Yang; Zhen Wang; Xiao Chen; Mengxia Fu; Mengda Xu; Yicheng Yang; Peizhi Wang; Chuangshi Wang; et al. (BMC Medicine)
Abstract Background Fibro-fatty replacement of the myocardium plays a key role in the pathogenesis of arrhythmogenic cardiomyopathy (ACM) and may be associated with progressive heart failure (HF). We aimed to investigate the characteristic of the fibro-fatty tissues of ACM patients and the plasma chemokines levels according to HF burden. Methods The expression level of markers for brown, beige, and white fat of fibro-fatty tissues was determined using a quantitative real-time polymerase chain reaction. Lipidomics analysis of fibro-fatty tissues (n = 10 for normal control [NC]; n = 24 for ACM patients) was conducted using LC–MS. Single-cell RNA sequencing (n = 2 for NC; n = 6 for ACM patients) was used to compare the immune environment in the myocardium. Immunostaining and enzyme-linked immunosorbent assay were used to examine the expression of CCL3 in the myocardium and plasma samples, respectively. Results The expression level of beige (TBX1 and TMEM26) and brown (TNFRSF9) fat markers were higher in the fibro-fatty tissues of ACM patients compared to NC. The fibro-fatty tissues revealed a significant increased level of saturated triglycerides (TGs) in ACM patients compared with NC. Single-cell RNA sequencing revealed the obvious accumulation of proinflammatory macrophages and a high expression level of proinflammatory markers in the myocardium of ACM patients compared to NC. The expression of CCL3 in the fibro-fatty tissues was positively correlated with HF progression in patients with ACM. Plasma CCL3 levels were significantly higher in patients with ACM compared to healthy volunteer. A total of 102 patients with ACM have been followed for a median of 7.8 years, indicating that plasma CCL3 levels could successfully predict the incidence of HF and heart transplantation (HTx)/death in patients with ACM (hazard ratio = 3.122 [95% confidence interval, 1.556–6.264]). The ROC curve analysis revealed the AUC value reached 0.814 for HF and 0.756 for HTx/death. Conclusions The increased level of saturated TGs and CCL3 in the fibro-fatty tissues might promote HF progression in ACM patients. Plasma CCL3 levels are useful for predicting HF-related adverse events in patients with ACM, but requiring further validation in larger and independent cohorts. Graphical Abstract